Cathepsin Cs are key for the intracellular survival of the protozoan parasite, Toxoplasma gondii. - Que, X; Engel, J; Ferguson, D; Wunderlich, A; Tomavo, S; Reed, S (2007)
Cysteine proteases play key roles in apicomplexan invasion, organellar biogenesis, and intracellular survival. We have now characterized five genes encoding papain family cathepsins from Toxoplasma gondii, including three cathepsin Cs, one cathepsin B, and one cathepsin L. Unlike endopeptidases cathepsin B and L, T. gondii cathepsin Cs are exopeptidases and remove dipeptides from unblocked N-terminal substrates of proteins or peptides. TgCPC1 was the most highly expressed cathepsin mRNA in tachyzoites (by real-time PCR), but three cathepsins, TgCPC1, TgCPC2, and TgCPB, were undetectable in in vivo bradyzoites. The specific cathepsin C inhibitor, Gly-Phe-dimethylketone, selectively inhibited the TgCPCs activity, reducing parasite intracellular growth and proliferation. The targeted disruption of TgCPC1 does not affect the invasion and growth of tachyzoites as TgCPC2 is then up-regulated and may substitute for TgCPC1. TgCPC1 and TgCPC2 localize to constitutive secretory vesicles of tachyzoites, the dense granules. T. gondii cathepsin Cs are required for peptide degradation in the parasitophorous vacuole as the degradation of the marker protein, Escherichia coli beta-lactamase, secreted into the parasitophorous vacuole of transgenic tachyzoites was completely inhibited by the cathepsin C inhibitor. Cathepsin C inhibitors also limited the in vivo infection of T. gondii in the chick embryo model of toxoplasmosis. Thus, cathepsin Cs are critical to T. gondii growth and differentiation, and their unique specificities could be exploited to develop novel chemotherapeutic agents.